Causes and occurring frequency of heavy rain, “unusual heavy rain” in the area from Hai Van Pass to Ca Pass, South - Central Region of Vietnam (period 1986 - 2010) - Vân, Nguyễn Khanh; Thủy, Đỗ Lệ; Đức, Trần Anh (Vietnam Journal of Earth Sciences, 2014)
Study on heavy rain and “unusual heavy rain” in the area from Hai Van Pass to Ca Pass, South - Central Region of Vietnam (period 1986-2010) shows that:- Statistically, in the studying area there are ∼ 3 heavy and very heavy rain spells annually (of which, there are ~1 very heavy rain spell). Rain spells often occur from August to November; but tend to concentrate in the period from October to December.- Heavy rains are caused by 7 types of synoptic weather situations (SWS). However, 4 following SWS have high frequency: Typhoon or Tropical Depression – 22.0%; Cold North-East monsoon – 20.5%; Typhoon (or Tropical 174 Depression) combined with Cold North-East monsoon – 19.2%; and Inter-tropical convergent combined with Cold North- East monsoon – 19.2%.- The combination of the above SWS at the same time or join together (one after another) can potentially cause heavy rain in large area and for a long time. Time of heavy rain spell can be varied from 2-6 days, but mainly: 2-4 days, the 5 days spell is limited, normally combined of main Cold North-East monsoon and additional one, or Inter-tropical convergent rain.- The SWSs are occuring in the midle of rain season (the months September -December, especially in October and December) often causing heavy and very heavy rains. These spells are often causing by Cold North-East monsoon combined strong East Wind Zone; Cold North-East monsoon combined Typhoon (Tropical Depression) or Inter-tropical convergent rain.- The SWS Typhoon (or Tropical Depression) made landfall in the studying area can resulting to heavy rain but not more then 3 days.- Besides heavy rains in the season, over 25 years (1986-2010) “unusual heavy rain” can occur 5 spells/25 years in period from January to July (∼ 0,2 “unusual heavy rain spell”/year), of which, there is only one “unusual very heavy rain” (∼ 0,04 “unusual heavy rain spell”/year)